Cebuano fiction Sugilanong sugboanon - Alburo, Erlinda Kintanar; Bandillo, Vicente; Dumdum, Simeon R.; Mojares, Resil B. (Ateneo de Manila University Press, 2009)
An anthology of prose fiction gathered from the mid-1800s until the year 2005. Each volume contains short stories or excerpts from short stories or novels in Cebuano.